Risk Assessment of Food Allergens. Part 1: Review and Validation of Codex Alimetarius Priority Allergen list Through Risk Assessment - Baumert, Joseph (2022)
The labelling of food allergens in pre-packaged foods plays a key role in protecting food allergic individuals, as no preventative clinical treatment is currently available. The list of major foods and ingredients known to cause hypersensitivity was included into the Codex General Standard for the Labelling of Packaged Foods (GSLPF) in 1999. There have been many scientific developments in the understanding of food allergens and their management since the original drafting of the GSLPF. Thus, in response to the request from Codex for scientific advice, including current evidence of consumer understanding of allergens, FAO and WHO convened a series of three expert meetings to provide scientific advice on this subject. The purpose of the first meeting of the Ad hoc Joint FAO/WHO Expert Consultation on Risk Assessment of Food Allergens was to review and validate the Codex priority allergen list through risk assessment. This report focuses on the deliberations and conclusions of this meeting. Resumen: El etiquetado de los alérgenos alimentarios en los alimentos preenvasados ​​juega un papel clave en la protección personas alérgicas a los alimentos, ya que actualmente no se dispone de un tratamiento clínico preventivo. Se incluyó la lista de los principales alimentos e ingredientes que causan hipersensibilidad en la Norma General del Codex para el Etiquetado de Alimentos Envasados ​​(GSLPF) en 1999. Ha habido muchos avances científicos en la comprensión de alérgenos alimentarios y su gestión desde la redacción original de la GSLPF. Por lo tanto, en respuesta a la solicitud del Codex de asesoramiento científico, incluida la actual evidencia de la comprensión del consumidor de los alérgenos, la FAO y la OMS convocaron una serie de tres reuniones de expertos para proporcionar asesoramiento científico sobre este tema. El propósito de la primera reunión de la Consulta Conjunta Especial de Expertos FAO/OMS sobre evaluación de riesgos de los alérgenos alimentarios fue revisar y validar la prioridad del Codex lista de alérgenos a través de la evaluación de riesgos. Este informe se centra en las deliberaciones y conclusiones de esta reunión.